Utility of prospective pathologic evaluation to inform clinical genetic testing for hereditary leiomyomatosis and renal cell carcinoma. Issue 13 (7th February 2017) - Kopp, Ryan P.; Stratton, Kelly L.; Glogowski, Emily; Schrader, Kasmintan A.; Rau‐Murthy, Rohini; Russo, Paul; Coleman, Jonathan A.; Offit, Kenneth
Abstract : BACKGROUND: Patients with hereditary leiomyomatosis and renal cell carcinoma (HLRCC) resulting from fumarate hydratase (FH) mutations may present with skin, uterine, and renal tumors, with each having unique pathologic features. This study investigated the association between prospectively identified suspicious pathology (SP) and FH mutations when patients were referred for genetic testing. METHODS: This was an institutional review board–approved cohort study of patients receiving FH testing from 2008 to 2013. SP was defined as a report of HLRCC histologic features identified during a prospective pathologic assessment. The association between SP and FH mutations was analyzed. RESULTS: FH testing was performed in 29 patients with a median age of 37 years; 15 (52%) were female, and 18 (62%) were white. Pathologists reported SP from kidney tumors (11 of 18), leiomyomas (9 of 15: uterus [n = 8] and bladder [n = 1]), and metastatic tumors (3 of 6) in 23 of 39 associated specimens (59%) from 21 of the 29 patients (72%). Patients with SP were younger (35 vs 51 years; P = .010), and those with kidney tumors more often had stage pT3 or higher renal cell carcinoma than those without SP (100% vs 33%; P = .006). FH mutations were present in 8 patients with SP (38%) and in 1 patient without SP (13%; P = .37); 7 of these patients had kidney cancer (n for SP = 7), all with N1 disease. Analyzing SP by tissue type identified only SP from renal tumors as being significantly associated with positive testing for an FH mutation ( P = .013). CONCLUSIONS: SP from kidney tumors was statistically associated with FH mutations. An expert pathologic assessment of renal tumors will facilitate the clinical identification of HLRCC cases, and this will result in genetic testing and targeted cancer screening for patients and at‐risk family members. Cancer 2017;123:2452–58. © 2017 American Cancer Society . Abstract : Prospective pathologic evaluation of kidney tumors may identify cases that are suspicious for hereditary leiomyomatosis and renal cell carcinoma–associated renal cell carcinoma, which remains a very lethal form of kidney cancer. In this series, cases with suspicious pathologic features are significantly associated with positive testing for fumarate hydratase mutations (diagnostic of hereditary leiomyomatosis and renal cell carcinoma) when they are referred for clinical genetic testing.